Aktivno i pasivno biračko pravo prema Ustavu Bosne i Hercegovine / Active and Passive Voting Law according to the BiH Constitution - Ajanović, Enver (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
Since the signing and entering into force of Dayton Peace Accords, constitutional changes in BiH have been the subject of debates. During these public hearings, the lack of understanding of the General Framework Agreement for Peace in BiH was evident, and Annex 4 to the Agreement in particular. The special problem poses the conclusion of this international Agreement in English. The BiH public has not always successfully coped with the meaning of linguistic nuances important for linguistic and other interpretations of the Constitution, primarily with the aim of adopting an amendment to the Constitution of BiH. These reforms should be adopted in accordance with the principle of pacta sunt servanda in the Vienna Convention on the Law of Treaties. In that sense, the Arbitration Award for the Brčko District of BiH, four judgments of the European Court of Human Rights, resolutions and recommendations of the Council of Europe and the EU enable the Constitution of BiH to remain an international agreement. This means that the will of the international community significantly determines the content of constitutional changes in BiH in accordance with the principle of the peoples’ right to self-determination in international law. In such changes, the institute of delegates in the House of Peoples of BiH, the House of Peoples of FBiH and the Council of Peoples of RS, wrongly called indirect elections, will disappear.